PERPETUAL LEASE: FEATURES OF ACCOUNTING - Yurchenko , T. V. (The actual problems of regional economy development, 2017)
The article namely deals with the peculiarities of legal regulation of the right to use someone else's land for agricultural purposes under the perpetual lease contract. Recognition of the legitimacy of perpetual lease as an intangible asset and, therefore, the object of accounting was justified. The features of the primary account perpetual lease rights were analyzed. It was found that for documenting transactions receipt, commissioning, de-recognition perpetual lease specialized forms of primary documents is not installed. The main aspects of accounting reflection of land under perpetual lease contracts were identified and ways of their improving were developed. The period on which the land is transferred for use under perpetual lease contract was proposed. During the study, general scientific methods – induction, deduction, synthesis, analysis, dialectical, historical, generalizations and specific methods of accounting – documentation, evaluation, accounting records were used.